The ancient mariner. (Economist, 2014)
The article reports on the 2014 effort by a group of amateur space scientists to reboot the International Sun/Earth Explorer 3 (ISEE-3) spacecraft which was launched in 1978 and was shut down by the U.S. National Aeronautics and Space Administration (NASA) in 1997. Topics include software developed specially for the project, citizen science, and the falling cost of satellites and their launches.